Analysis of cultural values in the folklore of Putri Mandalika - Fersa Maulida Al-Madia; Muhammad Ichsan (Mitra Palupi, 2022)
Background: Mandalika is used as an international event, where the name of the place comes from Lombok folklore. Purpose: This study aims to determine the cultural values ​​of the folk tale entitled Putri Mandalika which is found in Lombok, West Nusa Tenggara. Design & Methods: This research was conducted using a qualitative approach to content analysis methods with descriptive analysis techniques. The data source used is a document in the form of a book entitled Putri Mandalika folklore. Results: The results of the study revealed that there are three groups of cultural values ​​contained in the Putri Mandalika folklore, namely, cultural values ​​of human relations with nature, cultural values ​​of human relations with society, and cultural values ​​of human relations with other people.